Fasilitas MCK Di Ruang Publik Untuk Keperluan Warga Sekitar Dan Wisatawan - Hutahaean, Erik Saut H; Untari, Dhian Tyas; Soehardi, Soehardi; Sukreni, Tulus; Perdhana, Timorora Sandha; Khasanah, Fata Nidaul; Zulkarnaen, Iskandar; Thamrin, Djuni (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2021)
Muara Gembong district is often the attention of the surrounding community, especially the people of Jakarta and Bekasi. Its location directly facing the sea makes this sub-district often visited by various parties for travel or for other activities such as mangrove planting. There is one small problem but it is often considered as a very important thing related to the pattern of life of the community and also supporting infrastructure to lift tourism potential. One of the important is the availability of infrastructure that can be used by residents for bathing, washing and toilet purposes. Likewise for tourists, because it requires the infrastructure available. The results of discussions, interviews and field observations get there are three points that are quite ahagia ative to be able to overcome existing problems. Through the construction of MCK / Toilet infrastructure for the community and tourists are expected to have an impact related to efforts to lift the potential of tourism in muara gembong subdistrict. MCK / toilet development program also has an impact on the formation of healthy lifestyle patterns, and minimize environmental pollution whose source comes from human wastewater. The benefits of the program require continuous action from the community. Such as in the form of a cleanliness management system and its care.